2001
DOI: 10.4319/lo.2001.46.1.0038
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorometric characterization of dissolved organic matter for indication of precursor organic material and aromaticity

Abstract: We studied the fluorescence properties of fulvic acids isolated from streams and rivers receiving predominantly terrestrial sources of organic material and from lakes with microbial sources of organic material. Microbially derived fulvic acids have fluorophores with a more sharply defined emission peak occurring at lower wavelengths than fluorophores in terrestrially derived fulvic acids. We show that the ratio of the emission intensity at a wavelength of 450 nm to that at 500 nm, obtained with an excitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
1,869
9
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,494 publications
(1,967 citation statements)
references
References 33 publications
77
1,869
9
12
Order By: Relevance
“…FI values use the ratio of the emission intensities at 470/520 nm when the sample is excited at 370 nm (Cory and McKnight 2005). These ratios were shown to correlate well to the DOM precursor material as reported by McKnight et al (2001), who found respective larger and smaller FI values for autochthonous derived DOM (~1.9) and allochthonous DOM (~1.4). The samples were run using a SPEX spectrofluorometer at the University of Colorado in Boulder.…”
Section: Materials and Proceduressupporting
confidence: 61%
See 1 more Smart Citation
“…FI values use the ratio of the emission intensities at 470/520 nm when the sample is excited at 370 nm (Cory and McKnight 2005). These ratios were shown to correlate well to the DOM precursor material as reported by McKnight et al (2001), who found respective larger and smaller FI values for autochthonous derived DOM (~1.9) and allochthonous DOM (~1.4). The samples were run using a SPEX spectrofluorometer at the University of Colorado in Boulder.…”
Section: Materials and Proceduressupporting
confidence: 61%
“…The limited amounts of DOM isolated for this study prevented us from using more robust analytical methods capable of elucidating structure, e.g., 2-D NMR, FTICR-MS. Our parameters of choice, the fluorescence index values, are correlated to DOM source material and to a lesser extent aromaticity (McKnight et al 2001), whereas ε 280nm values are used to estimate aromaticity (Chin et al 1994). The DOM FI values do not show any significant trend related to a specific isolation technique (coefficient of error ±0.02) but do show that all the OWC isolates have a larger proportion of autochthonous material, as indicated by their overall higher FI values relative to the OKS samples (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Scan speed was 2400 nm min -1 and the bandwidth was set to 5 nm for both excitation and emission. UV absorbance and fluorescence data were used to calculate specific UV absorbance at 254 nm (SUVA 254 ) (Weishaar et al, 2003), fluorescence index (FI) (McKnight et al, 2001), humification index (HI) (Zsolnay et al, 1999), and common fluorescence EEM components (Fellman et al 2010). Three fluorescent EEM 185 components termed C1 (excitation/emission peaks at 325/467 nm), C2 (315/404 nm), and C3 (275/354 nm) were used to represent humic-like, microbial humic-like, and protein-like fluorescence, respectively (Fellman et al, 2010).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…According to the results of McKnight (2001), the ratio of the emission intensity at a wavelength of 450 nm to that at 500 nm (I 450 /I 500 = 35.2/21.5 = 1.6), obtained with an excitation of 370 nm, may reflect both terrestrial and microbial inputs in the Songhua River. According to the linear regression equation (McKnight et al, 2001): y = −0.027x + 2.1, r 2 = 0.85, the raw water DOM should have 18% aromatic content.…”
Section: Water Sourcesmentioning
confidence: 99%